Managing Food Imports for Food Security in Qatar - Simeon Kaitibie; Patrick Irungu; John N. Ng’ombe; Arnold Missiame (Economies, 2022)
Faced with food supply disruptions due in part to geopolitics and political instability in its traditional food source markets in the Kingdom of Saudi Arabia and the United Arab Emirates, Qatar—a wealthy, highly import-dependent open economy—plans to identify a set of alternative markets that can assure it of a stable food supply chain and food security. This study develops a set of preferences and import substitution elasticities for the country’s four most important food categories: meats, dairy, vegetables, and cereals. We used quarterly food import data from 2004 to 2017 and the Restricted Source-Differentiated Almost Ideal Demand System (RSDAIDS) to estimate import-substitution elasticities for meats, dairy, vegetables, and cereals imported by Qatar. Based on our findings, India, Australia, and the Netherlands emerged as Qatar’s most competitive sources of food, followed by Brazil, Jordan, and Argentina. Qatar can assure sustained demand for food imports from the aforementioned countries in order to address its food security.